Mangroves as a habitat for fish and prawns - Sasekumar, A.; Chong, V.C.; Leh, M.U.; D'Cruz, R. (Kluwer (now part of Springer), 1992)
Mangrove inlets and creeks in Selangor, Malaysia are the habitat for 119 species of fish and 9 species of prawns. The majority of fish and all prawns sampled in the inlets were juveniles. The common fish species in the inlets in terms of weight wereArius sagor, Ambassis gymnocephalus, Liza subviridis, Toxotes jaculator, Sphyraena barracuda andLates calcarifer. Prawns were represented by juvenilePenaeus penicillatus, P. merguiensis, P. indicus, Metapenaeus brevicornis andM. affinis. Samples from enclosure traps set on mudflats during ebbing water captured 37 species of fish and 11 species of prawns. The role of mangroves as nursery and feeding grounds for fish and prawns is reviewed in the light of recent work in Selangor. It is apparent that mangroves support fisheries by providing habitat and food.